Perinatal Risk Factors for Retinopathy of Prematurity in Preterm and Low Birth Weight Neonates - Yadav, Reena; Gupta, Sharad; Shrestha, Jyoti Baba; Yadav, Raveena; Yadav, Tushar Bikram Sipaliya (Nepalese Journal of Ophthalmology, 2020)
Background: Retinopathy of prematurity (ROP) is emerging as a leading cause of childhood blindness. The incidence of ROP is likely to increase after improvement in neonatal care unit in premature neonates. This study is conducted to determine the perinatal risk factors for ROP in preterm and low birth weight neonates. Methods: This is a prospective, descriptive and clinical; hospital based study. A total of 92 preterm neonates with gestational age of 36 weeks or less and birth weight of 2000 grams or less admitted in Neonatal Intensive Care Unit (NICU) were screened. Detailed antenatal, perinatal and neonatal history; birth asphyxia and subsequent oxygen support records were noted. All the neonates underwent detailed anterior and posterior segment eye examination with indirect binocular ophthalmoscope after pupil dilatation within 4 weeks of life. Retinal vascular changes were classified according to the International Classification of Retinopathy of Prematurity. The Chi-square test with odds ratio was performed to derive the association between ROP and antenatal, perinatal and neonatal factors. A p-value was considered significant at 0.05. Result: Out of 92 neonates, 21(22.8%) developed ROP. Twelve neonates (13%) had stage-1 ROP, 6(6.5%) had stage-2 and 3(3.3%) had stage-3 ROP. Birth weight (OR=2.9; p=0.04; 95% CI=1.0-8.3), gestational age (OR=3.9; p=0.01; 95% CI=1.3-11.8) and time span of oxygen exposure (OR=2.9; p=0.05; 95% CI=1.0-8.4) had a strong association with ROP. Conclusion: The incidence of ROP is significantly high among preterm low birth weight neonates. The risk of developing ROP becomes even greater with lower gestational age and more duration of oxygen exposure.